HUBUNGAN KADAR ESTRADIOL SERUM, INDEKS MASSA TUBUH (IMT) DAN UMUR DENGAN DENSITAS TULANG PADA WANITA PERIMENOPAUSE DAN PASCA MENOPAUSE - , NURDIANASARI DEWI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Osteoporosis has been responsible for 2.3 million fractures yearly in the world, and among Asian women, the Indonesian have the greatest risk for suffering from osteoporosis. Low body mass index (BMI), low estradiol level and higher age are predisposing factors for low bone mineral density (BMD). Objective: The study was undertaken to find out the relationship between menopausal status, age, estradiol level, and BMI to BMD. Method: The study was carried out at Sardjito Hospital from June to August 2011. Women during the peri-menopausal and postmenopausal period (age 45 to 90 years) were included into the study. Those with malignancy, hyperthyroidism, kidney diseases and those who had been done oophorectomy or under steroid hormonal therapy were excluded. BMD examination was done on Lumbar I to IV and pelvic bones using dual X-rays absorptiometry (DXA) at the Department of Radiology. Estradiol was examined using ECLIA methods. Low BMD was determined if the T-score was less than minus one (-1). Chi square test, correlation and multivariate linear regressions analysis were used for statistical analysis while SPSS was used for data processing Results: Among 85 women being eligible to the study, 72 (84,7%) were had been undergoing menopause and 60 (70.6%) had low BMD. The risk of getting low BMD was highest among menopausal compared to non-menopausal women (RR 3.43